-4n-6n+9=9

Simple and best practice solution for -4n-6n+9=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n-6n+9=9 equation:


Simplifying
-4n + -6n + 9 = 9

Reorder the terms:
9 + -4n + -6n = 9

Combine like terms: -4n + -6n = -10n
9 + -10n = 9

Add '-9' to each side of the equation.
9 + -9 + -10n = 9 + -9

Combine like terms: 9 + -9 = 0
0 + -10n = 9 + -9
-10n = 9 + -9

Combine like terms: 9 + -9 = 0
-10n = 0

Solving
-10n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '-10'.
n = 0.0

Simplifying
n = 0.0

See similar equations:

| 2y^3-32y^2-450y=0 | | 6/s=15/17.5 | | 6(6-3)-3= | | -14m-11=85 | | 2/3m-2=10 | | 2x=x-2+54 | | 975/195=p/1 | | (2y+8x)= | | -8(1+4x)-168= | | 48/96=g/6 | | 8+4=-4 | | 17-19=-2x | | (x-2)(x+3+3i)(x+3-3i)=0 | | 2y^3-10y^2-72y=0 | | 531/v=675/750 | | 9x-20=26x+30 | | 4y-18+y+14= | | 12Y=99 | | 539.4=x-231.1 | | 2q+24=26q | | 5a^2+19a=-30 | | 473/u=731/578 | | 9x^2+8=9 | | 121x^2-196=0 | | 2.5+x=-4.5 | | 2x^3-90x^2-392x=0 | | 17/b=85/50 | | 1.4x+3=9 | | 3x^2=-4+2x | | 4p-15=3p+6 | | 6y=-12x+30 | | 20/8=50/d |

Equations solver categories